Mapping of landslide vulnerability in the build area based on Remote Sensing and GIS in Ambon City, Indonesia - Lasaiba, Mohammad Amin; Gland Tetelepta, Edward; Salomo Leuwol, Ferdinand (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Landslides are natural hazards characterized by rock mass, debris, or soil movement on slopes under gravity. This study employed qualitative and quantitative methods with a spatial approach to analyze primary and secondary data obtained from satellite imagery, observations, and relevant institutions. Data were processed using Global Mapper 20, ArcGIS 10.8.1, and ER Mapper 8.1 software. The results obtained from this study revealed that the majority of the Ambon City area (approximately 51.63 %) was classified as having high landslide vulnerability. Meanwhile, only approximately 16.26% of the total area had very low or low landslide vulnerability. The same pattern is observed in built-up areas, where most landslide vulnerability falls under the high category (Z-4), at approximately 39.01%. In contrast, very low landslide vulnerability (Z-1) accounted for approximately 35.09%, and low vulnerability (Z-2) accounted for approximately 11.89%. The level of landslide vulnerability in the built-up areas also highlights that most of the Ambon City area, with mountainous terrain accounting for approximately 89% of the total area, experienced relatively high occurrences. In response, the government and relevant authorities must undertake careful spatial planning, direct development towards safer places, and implement policies that support sustainable development.